Separation of Auger transitions into different repulsive states after K-shell photoionization of N2 molecules - Cherepkov, N. A.; Semenov, S. K.; Schöffler, M. S.; Titze, J.; Petridis, N.; Jahnke, T.; Cole, K.; Schmidt, L. Ph. H.; Czasch, A.; Akoury, D.; Jagutzki, O.; Williams, J. B.; et al. (My University, 2009)
The Auger transitions to different repulsive doubly charged molecular ion states are separated by measuring the angular resolved photoelectrons and Auger electrons in coincidence in the molecular fixed frame. The separation is achieved by comparing the experimental Auger-electron angular distributions at different kinetic-energy release values with theoretical curves calculated for different final dicationic states.